Analysis of moral education values in the book 'minimalist life according to the prophet' by ratnani latifah - Rodina Silfi Khorutul Uyyun; Luluk Ifadah; Nur Alfi Muanayah; Muh. Hasbi Khilal Zuhri (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2024)
Education is a highly suitable medium for enhancing human personality and intelligence. To ensure that its implementation produces the desired generation, education is continuously developed and expanded. In relation to the current state of education, its quality, and the issues it faces, almost everyone agrees that religious education, especially Islamic education, which consists of aqeedah (faith) education, moral (akhlaq) education, and sharia (practical) education, serves as one of the means to address these problems. Moral education functions as a guide for character formation and as the main bulwark in upholding human morality. The objectives of this research include: to describe the values of moral education in the book 'Minimalist Life According to the Prophet' by Ratnani Latifah; to describe the minimalist lifestyle in the book 'Minimalist Life According to the Prophet' by Ratnani Latifah. This research uses a hermeneutic approach with the type of library research and a qualitative descriptive method. The data sources used are primary sources in the form of the printed book 'Minimalist Life According to the Prophet' and secondary sources such as books, journals, articles, the thoughts of the book's author, previous literature studies, and other scientific works focusing on the values of moral education. Furthermore, the data collection techniques include documentation and interviews. Finally, the data analysis uses content analysis techniques. The results of the research indicate that the values of moral education in the book 'Minimalist Life. According to the Prophet' include the values of moral education towards Allah, which encompass worship, asceticism (zuhud), trust in Allah (tawakal), gratitude, and sincerity. The values of moral education towards other people include contentment (qana'ah), humility (tawadhu), patience, being mindful of food and drink, simplicity, charity, visiting the sick, and attending invitations. The minimalist lifestyle taught in the book 'Minimalist Life According to the Prophet' includes appreciating every item owned, valuing experiences over possessions, freedom from clutter, and simplicity in lifestyle.